Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan Pada PT Toys Games Indonesia - Indah, Bella; Asmadi, Iwan (CV Warnak Johanna Nusantara, 2025)
Employee performance is a crucial component that can help a company succeed. This study aims to analyze how leadership style and work motivation impact the performance of employees at PT Sinergi Pari Jaya Abadi Tangerang. The research employs a quantitative statistical method. Primary data was collected through questionnaires distributed to 38 employees of PT Toys Games Indonesia. A saturated sampling technique, where the population size is equal to the sample size, was utilized. Data analysis was conducted using multiple linear regression with SPSS software. The results indicate a significant positive effect of leadership style on employee performance, with a t-value of 4.385, which is greater than the t-table value of 2.030, and a significance value of < 0.001. Additionally, work motivation also positively impacts employee performance, with a t-value of 3.743 and a significance value of < 0.001. Simultaneously, leadership style and work motivation positively influence employee performance, as evidenced by an F-value of 26.014, which exceeds the F-table value of 3.267. The coefficient of determination shows that leadership style accounts for 33.38% of the variance in employee performance, while work motivation accounts for 26.48%. These findings indicate that both variables significantly contribute to enhancing employee performance in the company.